AS RAÍZES ONTOLÓGICAS DO HOMO ECONOMICUS - Nunes Pires, Guilherme (Interfaces Científicas - Humanas e Sociais, 2024)
The aim of this paper is to identify the ontological origins of homo economicus in modern atomism to give a bigger picture of its origins. Homo economicus, the autonomous and independent economic agent, has been the central cornerstone of analysis in orthodox economic theories, and one of the most criticized hypothesis. The majority of studies try to understand its origins and consolidation in Economics analyzing the role of hipothetico-deductive model of reasoning and utilitarian philosophy influences in economists. However, we argue that the ontological roots of homo economicus are a necessary condition to understand it, since is primary force to build any science. The representative agent in Economics can trace to the resurgence of atomism as the ontological foundation of modern science, which lead to the establishment of modern individualism and reductionism.